STUDY ON GRAMMATICAL ERRORS IN ENGLISH SENTENCES WRITTEN BY THE SECOND GRADE STUDENTS OF SMA MUHAMMADIYAH 1 PRAMBANAN - Zulianti, Hajjah (Lentera: Jurnal Ilmiah Kependidikan, 2014)
This research entitled A Study on Grammatical Errors in English Sentences Written by the Second Grade Students of SMA Muhammadiyah 1 Prambanan is intended to find out the grammatical errors made by the second grade students of SMA Muhammadiyah 1 Prambanan and to find out the highest frequency of grammatical errors made by the students.This research is qualitative research. The object of this research is grammatical errors in English sentences. In collecting the data, the researcher uses testing technique. She gives the students some exercises, collects the studentsâ exercises, and puts the exercises into a research data file. In analyzing the data, the researcher applies descriptive qualitative method. The researcher reads the studentsâ English sentences. She observes the data carefully to find out grammatical errors. She takes note on the grammatical errors and then classifies and tabulates them based on the kinds of grammatical errors.The result of the study shows that the grammatical errors found in the studentsâ sentences deal with omission errors, addition errors, misformation errors, and misordering errors. The highest frequency of grammatical errors lies on the use of be form.